1989
DOI: 10.1038/338345a0
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in the α3 domain of HLA-A molecules affects binding to CD8

Abstract: Cytotoxic T lymphocytes (CTL) expressing the CD8 glycoprotein recognize peptide antigens presented by class I major histocompatibility complex (MHC) molecules. This correlation and the absence of CD8 polymorphism led to the hypothesis that CD8 binds to a conserved site of class I MHC molecules. Using a cell-cell binding assay we previously demonstrated specific interaction between human class I MHC (HLA-A,B,C) molecules and CD8. Subsequent analysis of the products of 17 HLA-A,B alleles revealed a natural polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
134
0
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 226 publications
(147 citation statements)
references
References 23 publications
11
134
0
1
Order By: Relevance
“…During T cell target engagement CD8 binds to the membrane proximal ␣3 domain of class I on the opposing cell. A naturally occurring single amino acid polymorphism in HLA-A68 and HLA-B48 abrogates this binding (25)(26)(27). Apparent in the CD8-HLA co-crystal this polymorphism distorts a protruding loop of the ␣3 domain, although the polymorphic residue at position 245 is not directly involved in contact with CD8 (26).…”
Section: Discussionmentioning
confidence: 99%
“…During T cell target engagement CD8 binds to the membrane proximal ␣3 domain of class I on the opposing cell. A naturally occurring single amino acid polymorphism in HLA-A68 and HLA-B48 abrogates this binding (25)(26)(27). Apparent in the CD8-HLA co-crystal this polymorphism distorts a protruding loop of the ␣3 domain, although the polymorphic residue at position 245 is not directly involved in contact with CD8 (26).…”
Section: Discussionmentioning
confidence: 99%
“…The a domain contains two regions that are implicated in binding CD8 molecules, amino acid positions 220-232 and 244-257 in HLA-A2, and the corresponding positions are 216-228 and 241-254 in duck alleles. In mammals, the presence of an alanine at position 245 is essential for CD8 binding and CD8 + T cell interactions (47), and this residue is conserved in ducks. We note the nonconservative substitution of a positively charged arginine or lysine for the negatively charged glutamine at position 226 within the CD8 binding region in several duck alleles.…”
Section: Expressed Alleles Have Features Of Classical Mhc Class I H Cmentioning
confidence: 99%
“…A range of experimental approaches reported in 1988-9, including co-immunoprecipitation studies, cell-cell-binding assays, and the use of artificial vesicles expressing purified CD8 or HLA molecules, definitively demonstrated that CD8 is a co-receptor of class I MHC [49][50][51]. The identification of class I MHC alleles with low CD8-binding affinity, coupled with sitedirected mutagenesis, revealed that CD8 binds the a3 domain of class I MHC molecules [52]. Thus, almost 15 years after the discovery that CD8 was associated with the lytic fraction of Thy-1-bearing lymphocytes, it was now not just a marker, but intimately tied to target recognition.…”
Section: The Enlightenmentmentioning
confidence: 99%